2016
DOI: 10.1103/physrevd.93.023002
|View full text |Cite
|
Sign up to set email alerts
|

Testing models of vacuum energy interacting with cold dark matter

Abstract: We test the models of vacuum energy interacting with cold dark matter and try to probe the possible deviation from the ΛCDM model using current observations. We focus on two specific models, Q = 3βHρΛ and Q = 3βHρc. The data combinations come from the Planck 2013 data, the baryon acoustic oscillations measurements, the type-Ia supernovae data, the Hubble constant measurement, the redshift space distortions data and the galaxy weak lensing data. For the Q = 3βHρc model, we find that it can be tightly constraine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 129 publications
(105 reference statements)
4
68
0
Order By: Relevance
“…This is the main result of the present investigation, and it is in agreement with the results of other observational works [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], however it has been arisen through the novel use of the recently released cosmic chronometers data.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…This is the main result of the present investigation, and it is in agreement with the results of other observational works [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], however it has been arisen through the novel use of the recently released cosmic chronometers data.…”
Section: Resultssupporting
confidence: 82%
“…Hence, many different scenarios of interacting dark energy have been constructed (see [7,8] for reviews and references therein). Interestingly enough, recently it has been shown that the current data might favor the late-time interaction between CDM and the vacuum energy [9][10][11][12] or the dynamical dark energy sector [13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the presence of an interaction in the dark sector could successfully reconcile the long lasting cosmic coincidence problem [3,4,5,6,7]. Following this, a number of investigations in the context of interacting DE -DM models were performed by many investigators [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43] (also see two review articles in this direction [44,45]). An interesting outcome from the interaction is that, it could naturally explain the phantom dark energy equation-ofstate [46,47,48,49].…”
Section: Introductionmentioning
confidence: 99%
“…where Q is the phenomenological interaction term [113][114][115][116][117][118][119][120][121][122], denoting the energy transfer rate between dark energy and dark matter. In this paper, we consider the following five cases in the IHDE model:…”
Section: The Interacting Model Of Holographic Dark Energymentioning
confidence: 99%